Contactless photoplethysmography for assessment of small fiber neuropathy - Marcinkevics, Zbignevs; Rubins, Uldis; Aglinska, Alise; Logina, Inara; Glazunovs, Dmitrijs; Grabovskis, Andris (Frontiers in Physiology, 2023)
Chronic pain is a prevalent condition affecting approximately one-fifth of the global population, with significant impacts on quality of life and work productivity. Small fiber neuropathies are a common cause of chronic pain, and current diagnostic methods rely on subjective self-assessment or invasive skin biopsies, highlighting the need for objective noninvasive assessment methods. The study aims to develop a modular prototype of a contactless photoplethysmography system with three spectral bands(420 nm, 540nm, and 800nm) and evaluate its potential for assessing peripheral neuropathy patients via a skin topical heating test and spectral analyses of cutaneous flowmotions. The foot topical skin heating test was conducted on thirty volunteers, including fifteen healthy subjects and fifteen neuropathic patients. Four cutaneous nerve fiber characterizing parameters were evaluated at different wavelengths, including vasomotor response trend, flare area, flare intensity index, and the spectral power of cutaneous flowmotions. The results show that neuropathic patients had significantly lower vasomotor response (50%), flare area (63%), flare intensity index (19%), and neurogenic component (54%) of cutaneous flowmotions compared to the control group, independent of photoplethysmography spectral band. An absolute value of perfusion was 20-30% higher in the 420 nm band. Imaging photoplethysmography shows potential as a cost-effective alternative for objective and non-invasive assessment of neuropathic patients, but further research is needed to enhance PPG signal quality and establish diagnostic criteria.